Synthesis of wheatear-like ZnO nanoarrays decorated with Ag nanoparticles and its improved SERS performance through hydrogenation. (26th February 2016) - Shan, Yufeng; Yang, Yong; Cao, Yanqin; Fu, Chaoli; Huang, Zhengren
Abstract: Semiconductor/noble metal composite SERS substrates have been extensively studied due to their unique bifunctionality. In this work, wheatear-like ZnO nanoarrarys have been fabricated via a modified low-temperature solution method. The hierarchical nanostructures that are constructed by stacked nanoflakes and long whiskers of ZnO possess a substantial number of characteristic nano corners and edges, which are proved to be beneficial to deposit more Ag nanoparticles (NPs). Furthermore, hydrogenated wheatear-like ZnO/AgNP composite substrates are achieved via a safe and facile solid hydrogen source (NaBH4 ). The hydrogenated ZnO/AgNPs (H-ZnO/Ag) substrates exhibit greatly improved SERS activity in detecting R6G molecules with an enhancement factor (EF) up to ∼0.49 × 10 8, over two orders of magnitude higher than that of the substrates before hydrogenation. The outstanding SERS performance of wheatear-like H-ZnO/Ag substrates benefits from the emerging porous structure of ZnO and abundant surface defects introduced by hydrogenation. In addition, the as-prepared substrates also show high detection sensitivity, good repeatability and recyclability, indicating great potential for practical applications.